Validity of the Framingham Risk Model Applied to Japanese Men - Suka, M.; Sugimori, H.; Yoshida, K. (Methods of Information in Medicine, 2002)
Objectives: To examine whether the Framingham Risk Model can appropriately predict coronary heart disease (CHD) events detected by electrocardiography (ECG) in Japanese men.Methods: Using the annual health examination database of a Japanese company 5611 male workers, between the ages of 30 to 59, who were free of cardiovascular disease, were followed up to observe the occurrence of CHD events detected by ECG over a period of five to seven years. The probability of CHD was calculated for each individual from the equations of the Framingham risk model (with total cholesterol).Results: The incidence of CHD increased with the estimated CHD risk. The Hosmer-Lemeshow goodness of fit test showed an adequate fit of the risk model to the data of the study subjects. In the receiver operating characteristic analysis, the area under the curve reached 0.67 which indicated an acceptable discriminatory accuracy of the risk model.Conclusions: The Framingham risk model provides useful information on future CHD events in Japanese men.
Keywords: Follow-up study; risk; coronary disease; electrocardiography; Japan; men